The effect of socioeconomic deprivation on 12 month Traumatic Brain Injury (TBI) outcome. (23rd February 2020) - Humphries, Thomas Jackson; Ingram, Sarah; Sinha, Saurabh; Lecky, Fiona; Dawson, Jeremy; Singh, Rajiv
ABSTRACT: Objectives : To assess the impact of social deprivation on Traumatic Brain Injury (TBI) global outcome. Design : The study was a prospective observational study conducted using consecutive admissions with TBI. Subjects : 1322 consecutive adult patients with TBI were recruited into the study between 2010 and 2015. Methods : All patients were assessed by the TBI rehabilitation team at both six weeks and 12 months following TBI. Details of the injury and demographic data was collated at six weeks. This included age, gender and ZIP Code. Social deprivation was measured by the Indices of Multiple Deprivation (IMD) Score. The outcome measure used was the Extended Glasgow Outcome Score (GOSE) at 12 months. Univariate analysis was followed by a Multi-Ordinal Regression to evaluate predictor variables. Results : With regard to the representation of IMD deciles, the study population approximated to the general Sheffield population ( p = .139). Within the univariate analysis, statistically significant relationships were noted between IMD and GOSE ( p = <.001). The Ordinal Regression revealed a significant relationship between worse GOSE and IMD ( p = .002), age ( p = .001), GCS ( p < .001), alcohol intoxication ( p < .001) and Medical Comorbidity ( p = .041). Conclusion : Increasing social deprivation is associated with poorer global TBI outcomes at 12 months.